Sleeping paralysis prevalence and presentation in human medicine students - Huamaní, Charles (2006)
Objective: To determine life prevalence and characteristics of sleeping paralysis in San Marcos University human medicine fourth year students. Design: Observational, descriptive, crosssectional study. Setting: Faculty of Medicine, San Marcos Major National University. Participants: One hundred thirty nine fourth year medicine students. Interventions: Life and characteristics sleeping paralysis non-concurrent longitudinal study for incidence density, done in August 2005, using a survey type questionnaire validated by experts. Main outcome measures: Sleeping paralysis life prevalence, characteristics, and one month prevalence in medical students. Results: Life prevalence was 56%; prevalence in the last month was 33 events per 100 students; 83,2% had hallucinations during the sleep paralysis events, 58,8% experienced anxiety. Remission was usually spontaneous (64,4%). Conclusions: The prevalence of sleeping paralysis in medical students is greater than that reported in previous investigations, with a high percentage of hallucinations and anxiety.